Rancang Bangun Sistem Inventory Data Barang Berbasis Web - Widyastoety, Dahlia (Jurnal Inovatif : Inovasi Teknologi Informasi dan Informatika, 2020)
PT Graha Sarana Duta established since 1981 engaged in providing office building, building maintenance and maintenance services. At present the system is still manual which causes the company's performance to be hampered and has not been able to support all the needs of the company such as a report that is long enough to report so that management waits long to get it. This study aims to analyze and design a web-based inventory system that can present the information needed by the company. Operations that run on this system are: input data for outgoing goods, input data for incoming goods, input data for supplier, work order, incoming goods report, outgoing goods report, ready stock report,work order report and goods check. The development tools used in this research are using PHP.5.2.2 as a programming language and MySQL version 5.0.41 as the database, these were all chosen because of their reliability in making a web-based system. Design and design an inventory system for PT Graha Sarana Duta. This Inventory system is web based so it is more dynamic and can be used easily. The system is used to manage data items that occur in the warehouse with various menus available.